Collection of Land & Building Rights Acquisition Fees (BPHTB) based on Transaction Price in Land & Building Sales-Purchases in Batang Regency - Apri Yahya, Muhammad; Ispriyarso, Budi (Law Development Journal, 2025)
Collection of Land and Building Acquisition Tax (BPHTB) is required to obtain land and building rights, it is mandatory to pay BPHTB tax. Therefore, a thesis was compiled with the title "Collection of Land and Building Acquisition Tax (BPHTB) Based on Transaction Prices in Land and Building Sales and Purchases in Batang Regency". The formulation of the research problem is, (1) How is the collection of BPHTB at the office of the Regional Financial, Revenue and Asset Management Agency (BPKPAD) of Batang Regency, (2) How is the alignment of the determination of the transaction price as the basis for determining the acquisition value of the tax object (NPOP) with the regulations and laws in the imposition of BPHTB, (3) What are the obstacles and solutions that occur in the implementation of tax collection (BPHTB) on the transaction price of land and building sales and purchases that have increased drastically in Batang Regency. The approach method used in this study is empirical juridical, with descriptive analytical research specifications. The data used are primary data and secondary data, primary data was obtained by interviewing the Head of the Sub-Division of Services and Determination of BPKPAD Batang Regency and secondary data was obtained by means of literature study. After all the data was obtained, it was then analyzed using qualitative methods. The results of the study for the collection of BPHTB taxes in Batang Regency used a self-assessment system which means that Taxpayers are required to calculate, calculate, pay themselves and report the taxes owed in accordance with tax laws and regulations, so that the determination of the amount of tax owed is entrusted to the Taxpayer. In the Regional Regulation of Batang Regency Number 8 of 2023 concerning Regional Taxes and Regional Retributions, it is stated that the basis for imposing BPHTB and Buildings is the transaction value. The obstacle in managing BPHTB is that there are still taxpayers who do not understand how to use BPHTB. And there are several implementing regulations that can be said to be less detailed so that they cause confusion, one of which is in terms of field verification, the BPKPAD also does not have a Regional Tax Determination Letter (SKPD) that is competent in assessing the value of Tax Objects owed by BPHTB. Keywords: Land and Building Acquisition Tax (BPHTB), Land Sale and Purchase,Transaction Price.